2021
DOI: 10.1002/rrq.398
|View full text |Cite
|
Sign up to set email alerts
|

Reading Anxiety, Engagement, and Achievement: A Comparison of Emergent Bilinguals and English Monolinguals in the Elementary Grades

Abstract: Socioemotional constructs have been receiving increased attention as contributors to individuals’ literacy development. However, in comparison with positive socioemotional constructs, negative socioemotional constructs have been understudied with respect to their role in reading achievement in both emergent bilinguals (EBs) and English monolinguals (EMs). In the present study, we addressed this gap by examining reading anxiety in 339 EBs, who primarily spoke Spanish as their first language, and 178 EMs in grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Based on the information provided, there is a high correlation between students' use of reading strategies and their engagement. Taboada (2021) [19] explored the relationship between successful task completion, cognitive reading, and intrinsic motivation among students. The findings revealed a significant positive correlation between successful task completion, cognitive reading abilities, and intrinsic motivation.…”
Section: Relationship Between Reading Strategies and Engagement In En...mentioning
confidence: 99%
“…Based on the information provided, there is a high correlation between students' use of reading strategies and their engagement. Taboada (2021) [19] explored the relationship between successful task completion, cognitive reading, and intrinsic motivation among students. The findings revealed a significant positive correlation between successful task completion, cognitive reading abilities, and intrinsic motivation.…”
Section: Relationship Between Reading Strategies and Engagement In En...mentioning
confidence: 99%
“…Reading anxiety is rooted in repeated negative emotional, cognitive, and physiological reactions related to reading (Jalongo & Hirsh, 2010;Piccolo et al, 2017) including perceived or actual critical reaction from others about one's reading skills that may result in a reduction of reading motivation and involvement (Jalongo & Hirsh, 2010). For children with reading anxiety, reading comprehension can be an intimidating process (Barber et al, 2022). Macdonald et al (2021) found a small but statistically significant unique contribution of reading anxiety (2.3%) to reading comprehension.…”
Section: Affective Factors Related To Reading Acquisitionmentioning
confidence: 97%